Research in Applied Linguistics and Language Education : Design, Methods and Analysis - POPESCU, Teodora (Presa Universitară Clujeană, 2025)
Whether you are a doctoral candidate in applied linguistics, an MA student in language education, or a classroom practitioner seeking to improve teaching through action research, you should find a place for yourself here. The structure and content are designed to be accessible yet rigorous—familiar enough to use, but rich enough to extend your thinking.